Duração dos segmentos vocálicos orais, nasais e nasalizados do português brasileiro - Hellen de Oliveira Valentim (2009)
This dissertation aimed at investigating the influence of voice quality, nasality, manner and place of articulation of the subsequent consonant on the duration of vowels /a/, /i/ e /u/ without including the measure of the nasal murmur, when present and on the nasal murmur itself. Spectrographic analysis of sounds was used to obtain the data. The study included 15 men aged over 18 years old. Results showed that even without the inclusion of the extent of the nasal murmur, nasal vowels had longer durations than their oral counterparts. The duration of the vowel depends not only on the nasality, but the voice quality, the manner of articulation of the subsequent consonant and the point of articulation of the subsequent consonant. The presence and duration of nasal murmur did not depend on the voice quality or the point of articulation of the subsequent consonant. The presence of nasal murmur depended on themanner of articulation of the subsequent consonant. The findings indicated that the inclusion of nasal murmur in the duration of nasal vowels may be unnecessary.